TINJAUAN LITERATUR : MODEL STRATEGI KOMUNIKASI PEMASARAN DIGITAL PADA USAHA MIKRO KECIL DAN MENENGAH - Fristaloka, Gina Dwi; Soegoto, Eddy Soeryanto; Wahdiniwaty, Rahma; Sumitra, Irfan Dwiguna; Bachtiar, Adam Mukharil (Majalah Ilmiah UNIKOM, 2025)
The rapid development of technology today, especially in digital marketing for Micro, Small and Medium Enterprises (MSMEs), often causes MSME players to experience confusion in determining the priorities for using this technology. The abundance of technology tends to be underutilized by MSME players in developing their businesses. This study aims to develop a strategic model applied to an effective technology roadmap for MSMEs to enhance their competitiveness. The methodology employed in this research is based on a systematic literature review of reputable scientific articles published in the last five years (2020-2025). The results of the study formulate a roadmap model consisting of four crucial stages: (1) The foundation & readiness phase, which focuses on legality and financial literacy; (2) The transaction & capital access phase, which emphasizes the adoption of marketplaces and digital payments; (3) Engagement & Ethics Phase, which prioritizes creative content and storytelling; and (4) Integration & Sustainability Phase, which implements CRM and supply chain management. This study concludes that marketing communication strategies in the digital era cannot be implemented simultaneously. The main implication of this study emphasizes that digital marketing failures are often caused by weak foundations. Therefore, MSMEs are advised not to jump straight into complex technologies without first addressing legal and operational fundamentals to ensure business sustainability. Key Words: Digital marketing, Marketplace, MSME, Roadmap, Social Commerce